Assessing the readiness of selected departments at Al-Baha University to integrate artificial intelligence applications in E-learning - Alowayr, Ali (Edelweiss Applied Science and Technology, 2025)
As artificial intelligence (AI) continues to redefine educational practices worldwide, universities are increasingly exploring its potential to enhance the effectiveness and quality of e-learning environments. This study aims to assess the readiness of selected departments at Al-Baha University, Saudi Arabia, to integrate AI applications into e-learning by examining the current status of digital learning, institutional capabilities, faculty knowledge, and perceived challenges. Using a descriptive research design, data were collected through structured electronic questionnaires administered to 95 faculty members and 53 e-learning staff, and analyzed using descriptive statistics. The findings reveal that although e-learning implementation is currently strong and supported by ongoing institutional and technological development, the university’s preparedness for AI integration remains moderate, particularly in areas related to strategic planning and infrastructure. Faculty members expressed a high willingness to adopt AI tools but demonstrated only moderate levels of actual knowledge. Key barriers included limited training opportunities, lack of a clear institutional strategy, concerns about job replacement, and high implementation costs. Overall, the results indicate a positive inclination toward AI adoption while underscoring the need for strengthened training, strategic direction, and technological investment to ensure effective and sustainable integration of AI in e-learning.